PENGHAMBAT DAN PENDORONG GREEN SUPPLY CHAIN MANAGEMENT (Studi Kasus : Aluminium Formwork) - Agustinaputri Bintang Galaxy; M. Agung Wibowo; Suharyanto Suharyanto (Politeknik Negeri Semarang, 2021)
Technological innovation in the construction sector is needed not only aimed at faster construction but also environmentally friendly. Engineering the formwork system using aluminum is one of the technological innovations to accelerate development and adopt the 3R (Reuse, Reduce, and Recycle) concept. To support the use of aluminum formwork, an environmentally friendly supply chain activity management model is needed. The Green Supply Chain Management (GSCM) approach is one method that can reduce waste. This study analyzes the driving and inhibiting factors of GSCM using aluminum formwork in an apartment project in Semarang. The method of compiling this research used a qualitative method, where interviews were conducted which were then made into complete transcripts and grouped each opinion with a SWOT matrix approach. Based on the results of the SWOT analysis, 4 factors have a significant effect. Among these 4 factors, there are 2 driving factors, namely government regulations regarding environmental protection and commitment to protecting the environment, and 2 inhibiting factors, namely the availability of suppliers who implement GSCM practices in construction areas and require careful planning. The use of aluminum formwork can save costs up to 5.44% with a construction time of 6 days faster than conventional methods.